„Working class“ in the Modern Social Historical Writing - Pullmann, Michal; Rákosník, Jakub (Dějiny – teorie – kritika, 2022)
Current historical debates about class formation and collective identities in the modern societies point out the importance of the analytical category of class. The essay reconstructs various approaches to the category of class in the modern historical writing – based on differentiation and polarizing social structures (J. Kocka), class experience and class consciousness (E. P. Thompson), class discourse (G. Stedman Jones), „imaginary institution of society“ (P. Joyce). Upon these approaches, we employ different ways of historical explaining of the class formation to appreciate the issue of making and differentiation of normative patterns, allowing agents to identify suffering as a social phenomenon and opening new struggles for recognition.